Historical aspects of the emergence and development of family-type children’s home in the Ukrainian lands in the twentieth century - Свіжа, Ольга Олегівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2010)
The article discusses theoretical and practical problems of building and development of children’s family type in the Ukrainian lands in the twentieth century. Including legal forms of regulation of placement of orphans and children deprived of parental care and the practice of its application.